Analisis Pengembangan Bisnis melalui Pendekatan Business Model Canvas pada Pabrik Tahu Mbah Ran (Tukiran) - Achmad Biki; Rudeva Juniawaty (FOCUS, 2022)
The aim of the research is to analysis business development strategy with a Business Canvas Model at Mbah Ran’s (Tukiran) tofu factory. This research is use mix method with descriptive approach. The populations and the samples of this research are owner, emlpoyees, consumens and also the activities of the Mbah Ran’s tofu factory. Miles & Huberman’s Model will become the data technique analysis to process qualitative data and for the quantitave analysis researchers use SWOT methods. The results of this research are Mbah Ran’s (Tukiran) tofu factory has implemented business model concept which is already fullfill the requirements of the nine elements in Business Model Canvas. But in daily routines there are eight elements that must be evaluated for the development. The calculation results of Mbah Ran’s (Tukiran) tofu factory is in III quadrant of SWOT analysis, the opportunity of Mbah Ran’s (Tukiran) tofu factory is huge but in other side there is also an internal constraints. Based on the result of SWOT analysis, researchers make a right strategy that applied to Business Model Canvas.